Musings On Ars Poetica : Poetic Reflections on the Poet and Poetry in Verse. - Ndi, Bill F. (African Studies Centre research series., 2009)
A literary monument erected by a poet for poets with a vision for poetry as a special annunciation and the poet as a seer, spokesperson, recorder, analyst, adjudicator and advocate with poetic vision and poetic understanding. Bill Ndi, the poet has the rare gift of slipping into the self and psyche of his society to empty the dark depths where the treasures of burden and sadness are hidden. He empties and exposes them to the world to see how even personal repression of feelings by far outweighs those imposed throughout History by tyrants. It is above all, his greatest task of filling these dep.